A civil action - Harr,Jonathan (Arrow books, 1997)
The lawyer had not wanted the case at first - it was too big, too complicated, too risky. It concerned a cluster of childhood leukemia victims in a small town north of Boston where the city wells had been poisoned by industrial chemicals. Two of the nation's largest corporations, each with a plant near the wells, stood accused. Against his better judgment, the lawyer found himself drawn into the case. In this book,